2017
DOI: 10.3390/children4050037
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Maternal 25-OH Vitamin D Serum Levels in Neonates with Early-Onset Sepsis

Abstract: Vitamin D is a fat-soluble vitamin that is important for calcium metabolism and plays an important role in the immune functions. The aim of this study was to measure neonatal and maternal 25-OH vitamin D serum levels in neonates with early onset sepsis. The study included fifty neonates with early onset sepsis (25 full-term and 25 preterm infants) and thirty age and sex matched healthy neonates as controls. After history taking and clinical examination, complete blood count, C-reactive protein and 25-OH vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 36 publications
(58 reference statements)
2
25
1
1
Order By: Relevance
“…The commonest mode of delivery was cesarean section (92%) which higher than the results obtained by Gamal et al [19] who found that, CS was 72%. However, the results of the current study agree with Aye et al [12] who found no significant difference between cases and controls regarding mode of delivery.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The commonest mode of delivery was cesarean section (92%) which higher than the results obtained by Gamal et al [19] who found that, CS was 72%. However, the results of the current study agree with Aye et al [12] who found no significant difference between cases and controls regarding mode of delivery.…”
Section: Discussioncontrasting
confidence: 52%
“…Rass et al [17] found a significant difference sepsis and healthy groups regarding RBCs, PLT, WBC, neutrophil and CRP. In addition, Gamal et al [19] studied 50 neonates with EOS and reported significant decrease of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…26.4 ng/ml) 22. Gamal et al found not only significantly lower vitamin D levels in newborns with EOS as compared with controls, but also significant inverse correlations between vitamin D levels and all sepsis markers 23. Of note, all these studies reported a positive correlation between maternal and infant vitamin D levels.…”
Section: Discussionmentioning
confidence: 95%
“…Neonatal early-onset sepsis (case group; NEOS) consisted of 32 terms NICU hospitalized neonates as suspected sepsis in the patients’ group. EOS diagnosis was considered based on clinical and laboratory findings during the first 72 h of life to have a high potential NEOS according to the criteria defined by Soliman Gamal et al, 2017, such as temperature instability, heart rate dysrhythmia, poor feeding or intolerance, weight loss, abdominal distension, and necrotizing enterocolitis, and respiratory clinical signs containing distress, supplemental oxygen, mechanical ventilation requirement, apnea, tachycardia or bradycardia, and hypoxemia, as well as positive blood culture, elevates C-reactive protein (CRP) and hematologic cell blood count findings [17].…”
Section: Methodsmentioning
confidence: 99%